Maintaining Views as an Effort to Protect Oneself: Study of Takhrij and Syarah Hadith - Millah, Luthfatul; Moghaddas, Nafiseh Faghihi (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the hadith about maintaining views. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about keeping an eye on the history of Bukhari no. 6832. The results and discussion of this study indicate that the status of hadith is of authentic quality that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Bukhari no. 6832 is relevant to be used as a reminder to ourselves that maintaining that view is very important for personal benefit.